PTH-044 Improving safety and reducing error in endoscopy (ISREE) – a jag initiative. (8th June 2018) - Thomas-Gibson, Siwan; Matharoo, Manmeet; Siau, Keith; Sevdalis, Nick; Hawkes, Neil; Johnston, Debbie; Haycock, Adam; Green, John
Abstract : Introduction: JAG is committed to providing universal high quality and safe endoscopy as embedded in the Global Rating Scale. This requires acknowledgement that error is common, may not result in harm or complications, but that addressing latent risk can prevent patient safety incidents. Many errors relate to failures in human factors, ENTS and teamwork, which require training and assessment. Medical error is more prevalent in situations of complexity. Though generally safe, endoscopy is a complex task, performed in teams. As population demographics evolve, straight-to-test pathways become embedded and complex therapeutic options extended; endoscopists need to develop a proactive culture towards safety and learning from error. Aims: JAG aims to develop a work stream to Improve Safety and Reduce Error in Endoscopy (ISREE). A 1 day workshop was designed to develop an implementation plan to achieve this goal. Methods: 35 multi-disciplinary clinicians and a patient with specific expertise in this area were invited to ISREE workshop. Participants were asked to recall as many endoscopy adverse events or errors as possible. Key presentations highlighted the background to medical error, how to investigate it, development of non-technical skills frameworks (anaesthetics and endoscopy), safe sedation, human factors training and implementation science. A patient recounted her experiences of endoscopy. Facilitated group sessions focused on 5 key areas – improving training in ENTS and human factors, error prevention, reporting error, learning from error and managing underperformance (endoscopists, teams or units). Wider discussion synthesised a list of feasible actions that JAG could prioritise for staged implementation. Results: Multiple errors were reported by all delegates and recurrent themes were common. Examples related to wrong patient for procedure (n=4), histology mislabelling (n=5), drug errors (n=3) and failure to follow MDT advice (n=1). 23 key priorities were agreed and formulate an implementation strategy for JAG (table 1): Summary: JAG plans to develop a 5 y ISREE Implementation Strategy reflecting the identified priorities to 1) improve endoscopists training in effective error reporting and learning and 2) implement system level approaches to safety and performance improvement. JAG also aims to improve its communication to disseminate learning and support endoscopy services in the UK.